Analisis Nilai-Nilai Moderasi Beragama dalam Buku Ajar Al-Qur’an Hadis Madrasah Ibtidaiyah Terbitan Kemenag RI 2020 - Imronudin, Imronudin; Mubarok, Andi Husni (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research analyzes the values of religious moderation in the Al-Qur'an-Hadith Madrasah Ibtidaiyah (MI) teaching book published by the Ministry of Religion in 2020 for classes I-VI. Even though the teaching book includes moderate values, the delivery of the material is not optimal and needs further explanation so that students can receive it well. This research uses a qualitative descriptive method based on library research, categorizing themes related to religious moderation, frequency calculations, and conversion to percentages. The research results show that this book generally contains moderate values, such as civility (ta'addub), exemplary (qudwah), citizenship and nationality (muwatanah), taking the middle path (tawassuṭ), balance (tawazun), straight and firm (i'tidal), deliberation (syura), equality (musawah), tolerance (tasamuh), and dynamic and innovative (tathawwur wa ibtikar). However, these values are mostly not mentioned explicitly in textbooks. One of the values, deliberation (musyawarah), has not been found in the Basic Competencies (KD) or available materials.